PENGUKURAN KINERJA PENGGUNAAN TEKNOLOGI INFORMASI DI KEMENTERIAN KEUANGAN TIMOR-LESTE - de Fatima, Rosalino Pereira; Rosidi, Abidarin; Syahdan, Syamsul A (Jurnal Teknologi Informasi RESPATI, 2013)
IT is crucially need for sustaining performance of any organization, particularly in Computer information system inventories and IT management assessing using COBIT 4.1. One of COBIT advantage is it has been applied globally and published as open standard to be used by any organization for IT performance assessment and its goal is relevant. However, its scope is very wide thus it is not necessary to use its domain objective control comprehensively; we can select on DS domain according to company requirement.Present research objectives are to assess performance level of computer-based IT usage in T-L Finance Ministry within COBIT framework, identify COBIT-based IT managements, and providing recommendation for IT management that appropriate for Finance Ministry work and goals bases on KGI and KPI. This recommendation is expected adding consideration he IT management on how appropriately managing IT to sustain staff service performance, particularly IT service. The performance of computer-based IT in T-L Finance Ministry isÂ  drawn from analysis established by DS in COBIT framework. It reveals that DS 7 and DS 9 only achieved level 2 (two) of maturity, which means the process maturity not yet in expected level. IT management in T-L Finance Ministry had been perform optimally and gain maturity level on DS 1, 2, 3, 4, 5, 6, 8, 10, 11, 12, and 13; while DS 7 and 9 remain lack behind expectation. Â Keywords: IT Audit, IT Governance, COBIT, KGI & KPI, Maturity Model